Socio-Demographic Factors, Social Support, Quality of Life, and HIV/AIDS in Ghana. Issue 2 (3rd March 2016) - Abrefa-Gyan, Tina; Cornelius, Llewellyn J.; Okundaye, Joshua
Abstract : The increase in the access to biomedical interventions for people living with HIV/AIDS in the developing world has not been adequately matched with the requisite psychosocial treatments to help improve the effectiveness of biomedical interventions. Therefore, in this study the author seeks to determine whether socio-demographic characteristics and social support are associated with quality of life in individuals diagnosed with HIV/AIDS in Ghana. A convenience sample of 300 HIV/AIDS support group members was obtained via cross-sectional design survey. The Medical Outcome Studies (MOS) HIV Health Survey, the MOS Social Support Survey (MOS-SSS), and demographic questionnaire instruments were used to assess quality of life, social support, and demographic information respectively. Multiple regression analysis showed that there was a positive association between overall social support and overall quality of life ( r  = .51). It also showed that being younger, male, attending support group meetings for over a year, and having ≥ 13 years of schooling related to higher quality of life. Implications of the findings for practice, policy, and research in Ghana and the rest of the developing world are discussed.